Long QT syndrome - causes and risk factors - Ciechański, Erwin; Ciechańska, Magda; Ciechański, Krystian; Szponar, Jarosław (Journal of Education, Health and Sport, 2018)
Sudden cardiac death is a major public health challenge, which can be caused by genetic or acquired structural or electrophysiological abnormalities. These abnormalities include channelopathies such as long QT, short QT and Brugada syndromes. Long QT syndrome is a cardiac repolarization disorder and is associated with an increased risk of torsades de pointes (TdP). Main causes of acquired syndrome are specific medications and/or electrolytes imbalance. On the other hand common congenital causes are Jervell and Lange-Nielsen or Romano- Ward syndromes. Patients with risk factors, treated with specified QT prolongating drugs always require slow dose titration and electrocardiography monitoring. Aim of this study is to comprehensively and critically review the pathomechanisms of QT prolongation, risk factors and prevention methods.